Ambient PM2.5 and Related Health Impacts of Spontaneous Combustion of Coal and Coal Gangue - Guo, Wenkai; Chen, Bing; Li, Guangyao; Liu, Mingyue; Liu, Xiao; Chen, Qiang; Zhang, Xiaorui; Li, Shixue; Chen, Siyu; Feng, Wuhu; Zhang, Ruixin; Chen, Mei; et al. (Environmental Science & Technology, 2021)
Coal and coal gangue spontaneous combustion (CGSC) occurs globally, causing significant environmental pollution. However, its emissions are poorly quantified and are overlooked in global or regional air pollutant emission inventories in previous studies, resulting in the underestimation of its impacts on climate, environment, and public health. This study quantified the emissions of various air pollutants originating from CGSC in Wuhai, a city in China, investigated emission characteristics, and estimated the contribution of CGSC emissions to fine particulate matter (PM2.5) air pollution and related health impacts on a regional scale. The results revealed that the CGSC-related PM2.5 emissions were approximately 4643 t a–1 (95% confidence interval (95% CI): 721; 10447), accounting for 26.3% of the total PM2.5 emissions. Alkanes, alkenes, and aromatics accounted for 69.4, 17.9, and 2.9%, respectively, of the total emissions of volatile organic compounds (VOCs). Due to CGSC emissions, the ambient PM2.5 concentration in Wuhai increased by 5.7 μg m–3 on average, while the nitrate concentration decreased. The number of premature deaths caused by exposure to ambient PM2.5 associated with CGSC reached 381 (95% CI: 290; 452) in Wuhai and surrounding cities in 2017. Urgent control strategies and engineering techniques are needed to mitigate CGSC to protect public health.